Gynaecologic History During Adolescence to Predict Endometriosis Earlier - Hartati; Dwiana Ocviyanti; Ramzi Amin; Yusuf Effendi; Zen Hafy; Radiyati Umi Partan; Rafika Novianti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Endometriosis is a chronic gynecological disorder that generally affects women of reproductive age which is characterized by implantation of endometrial tissue, both glands and stroma outside the uterus. Research shows that the initial onset of endometriosis patients begins in adolescence. The high prevalence with atypical symptoms leads to long term delay in establishing the appropriate diagnosis. Further developments in the field of early endometriosis screening will greatly assist clinicians, especially general practitioners in areas with limited health facilities, in early detection of endometriosis. Methods. Using the electronic databases, comprehensive literature searches were conducted with the specific keywords. Full-text manuscripts published were reviewed for relevancy and importantly, reference lists were cross-checked for additional relevant studies. Results. Dysmenorrhea, chronic pelvic pain, dyspareunia, dysuria, dyschezia, and glycoprotein were found dominantly in all analyzed literature. The occurrence of endometriosis affects the functioning of women in multiple aspects of life. Endometriosis places a significant burden on teens and adult women, their families, and society as a whole. Conclusion. Combination of structured past history taking, and several biomarker level might be useful as a screening tool that easy to use and cost effective, as early diagnosis is expected to prevent further progression of endometriosis especially in adolescence.